CHAIRMAN CHARACTERISTICS AND CEO TURNOVER: EVIDENCE FROM UK LISTED FIRMS (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
The characteristics of chairman has been widely discussed since the introduction of the Cadbury Report. However, most discussions are related to separation chairman and CEO. Therefore, this study examines the influence of the other chairman characteristics, namely age, tenure, function, independence, and involvement in CEO selection, on CEO turnover. The results indicate that function, age and tenure have important role in explaining CEO turnover. The study concludes that certain chairman characteristics will lead to better corporate governance.Â Keywords: CEO turnover, Chairman Characteristics, Corporate Governance